Production of Consumer Goods by Industry of Middle Urals in 1971—1980 - V. N. Mamyachenkov; E. S. Kulikova; M. I. Lvova (Научный диалог, 2022)
The relevance of the study is due to the enduring theoretical and practical interest shown by Russian society in the historical period studied in the article. The novelty of the study is seen in the fact that the materials from the funds of two regional archives are used in the article: the Current Archive of the Territorial Authority of the Federal State Statistics Service for the Sverdlovsk Region and the Center for Documentation of Public Organizations of the Sverdlovsk Region, some of which are introduced into scientific circulation for the first time. It is emphasized that the decade under study was the peak of the historical period known as “stagnant”, becoming the last relatively prosperous decade in the history of the USSR. The authors state that the policy of “détente” provided the country with a certain foreign policy stability. Attention is focused on the fact that the development of stagnation phenomena in the country’s economy in the 1970s is clearly visible when analyzing the production of consumer goods on the example of almost any of its regions, including the Middle Urals. It is proved that during the decade under study there was no significant improvement in providing the population of the region with industrial food products. It is concluded that similar stagnation phenomena were observed in most and other areas of consumer goods production.